Kiat Pengelola Wisata Kuliner Seafood Dalam Memberikan Pelayanan Kepada Wisatawan Di Pantai Kedonganan - Yukitasari, I Gusti Ayu Putri; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p29, 2018)
Kedonganan beach is located in the village sub-district of Kedonganan Kuta, Badung Regency, Bali. Kedonganan beach has had a great revolution in the tourism development. Therefore, tourists always come to visit this beach. With a lot of tourists come, make the owner of tourism bussiness in the beach Kedonganan should be able to regulate and maintain the attitude in providing services to tourists. The purpose of this research is to know the approach of seafood culinary tour manager in providing services to the tourists. The method used to collect the data in this study are observation, interview, and literature study and the method used to analyze the data is qualitative descriptive analysis technique. The result of this research is the managers of the 4 selected cafes have different approach in providing services to tourists. The approach are such as service procedures , language learning and environmental cleanliness. From all of the approaches, although there is similar approach but they have different ways for the service provided. With the best services provided to tourists it is certain that Kedonganan beach will not lose tourists and can survive for long periods of time. Keywords : Management, Culinary Tourism, Hospitality